Efforts to Improve Learning Outcomes in PAI Husnuzhon Material Through Non-Directive Learning Models - Muhammad Al fathoni; Ahmad Sabri; Sasmi Nelwati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The aim of this research is to determine the impact of using a non-directive learning model on PAI learning outcomes in husnuzhon material after implementing the non-directive model. This type of research is classroom action research. There are four stages in each cycle, namely preparation, activity and observation, and reflection. The research subjects were eighth grade students. Based on the analysis of the researchers' findings, student work results increased from cycle I to cycle III, namely cycle 1 (60%), cycle II (78%) and cycle II (95%). It can be concluded that using this learning model can be used as an alternative learning method for Islamic Religious Education. As a suggestion, implementing PAI learning using a non-directive model requires thorough preparation for both teachers and students.